A Brief Motivational Interview Intervention to Reduce Dating Abuse Perpetration, Boston, Massachusetts, 2014-2017 - Rothman, Emily F. ([Verlag nicht ermittelbar], 2020)
This study tests a brief intervention designed to reduce adolescent dating abuse (ADA) perpetration in a healthcare setting used primarily by low income, Black, and Hispanic youth. The Project READY (Reducing Aggression in Dating Relationships for Youth) is a theory-driven, empirically supported, brief intervention. READY intercepts youth who utilize an urban emergency department for non-urgent health care (e.g., sprains), provides them with tailored feedback about their relationship behavior, and uses motivational interviewing to move them towards non-violence and respect. READY was designed to avoid victim-blaming and is responsive to the gendered dynamic of ADA. A small feasibility pilot test of READY was completed in 2013 (N=27). Participants were 173 youth ages 15-19 years old who were patients of an urban pediatric emergency department. Youth who perpetrated at least 1 act of physical or sexual ADA 3 months prior to baseline were eligible. The proposed experimental evaluation of READY used a randomized controlled trial (RCT) design, with 3- and 6-month follow-ups to assess changes in knowledge, attitude and perpetration behavior. The hypotheses are: (1) Youth who participate in the brief intervention session and telephone booster call will report improved knowledge and attitudes, and less self-reported ADA perpetration up to 6 months post-intervention as compared to youth in the control group; and (2) the cost of providing the intervention will be less than the cost of the violence that occurs in its absence. Mixed effects linear and logistic models were used to analyze longitudinal data.